Intranasal Oxytocin Treatment Increases Eye-Gaze Behavior toward the Owner in Ancient Japanese Dog Breeds - Nagasawa, Miho; Ogawa, Misato; Mogi, Kazutaka; Kikusui, Takefumi (Frontiers in Psychology, 2017)
Dogs acquired unique cognitive abilities during domestication, which is thought to have contributed to the formation of the human-dog bond. In European breeds, but not in wolves, a dog’s gazing behavior plays an important role in affiliative interactions with humans and stimulates oxytocin secretion in both humans and dogs, which suggests that this interspecies oxytocin and gaze-mediated bonding was also acquired during domestication. In this study, we investigated whether Japanese breeds, which are classified as ancient breeds and are relatively close to wolves genetically, establish a bond with their owners through gazing behavior. The subject dogs were treated with either oxytocin or saline before the starting of the behavioral testing. We also evaluated physiological changes in the owners during mutual gazing by analyzing their heart rate variability (HRV) and subsequent urinary oxytocin levels in both dogs and their owners. We found that oxytocin treatment enhanced the gazing behavior of Japanese dogs and increased their owners' urinary oxytocin levels, as was seen with European breeds; however, the measured durations of skin contact and proximity to their owners were relatively low. In the owners' HRV readings, inter-beat (R-R) intervals (RRI), the standard deviation of normal to normal inter-beat (R-R) intervals (SDNN), and the root mean square of successive heartbeat interval differences (RMSSD) were lower when the dogs were treated with oxytocin compared with saline. Furthermore, the owners of female dogs showed lower SDNN than the owners of male dogs. These results suggest that the owners of female Japanese dogs exhibit more tension during interactions, and apart from gazing behavior, the dogs may show sex differences in their interactions with humans as well. They also suggest that Japanese dogs use eye-gazing as an attachment behavior towards humans similar to European breeds; however, there is a disparity between the dog sexes when it comes to the owners' oxytocin secretion. Japanese dogs also showed different attachment behaviors from both European breeds and wolves, and they likely use additional strategies to substitute gaze when forming the human-dog bond.